Analisis Kerentanan Usaha Mikro Kecil Akibat Pandemi Covid-19 di Kabupaten Sumedang - Nugrahana Fitria Ruhyana (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2021)
Micro and small enterprises (MSEs) are most vulnerable to the Covid-19 pandemic. Many MSEs in Sumedang Regency are less adaptive when there are social restrictions so that their turnover decreases and some even close their businesses. A proper policy from the Sumedang Regency government is needed to overcome this problem, one of which is through a vulnerability analysis so that it can be seen which areas are most prone to the Covid-19 pandemic, especially from the socio-economic aspects related to MSEs. This study uses a spatial-based quantitative descriptive method with scoring techniques on each determining variable in the vulnerability analysis adopted from the Intergovernmental Panel for Climate Change (IPCC). The data used is Potensi Desa (village potential) in 2018 and 2019 as well as some supporting data from related agencies. The results of the vulnerability analysis show that there is one sub-district with a very high level of vulnerability, namely Jatinangor District, due to the large number of MSEs and most of the livelihoods of its population from sectors affected by social restrictions due to the Covid-19 pandemic such as industry, trade and services. Efforts that can be made to increase resilience to the Covid-19 pandemic at the regional level are by increasing adaptive capacity, especially encouraging economic activity at the village level through increasing Villlage-owned enterprises (BUMDES) business units and business scale, expanding internet signal coverage, and encouraging the expansion of the goods delivery service network.